1989
DOI: 10.1159/000199879
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ranitidine on Taurocholate-, Ethanol-, and Indomethacin-Induced Damage to Gastric Epithelial Cells in vitro

Abstract: We evaluated whether ranitidine protects gastric epithelial cells against damage induced by sodium taurocholate, ethanol or indomethacin, under conditions independent of its acid inhibitory effect as well as of systemic factors. We also studied the role of prostaglandins and sulfhydryls in any such protection. Ranitidine significantly reduced the amount of damage induced by taurocholate, but did not afford protection against ethanol- and indo-methacin-induced damage. Incubation with ranitidine did not increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The mechanism of action of ranitidine is well known. Furthermore, an in vitro study confirmed that H 2 blockers such as ranitidine have limited cytoprotective ability independent of acid secretion [42]. Figure 3 shows MDA concentration in normal gastric mucosa and in gastric mucosa of non-pretreated rats and rats pretreated with OLE and ranitidine.…”
Section: Effect Of Ole Pretreatment On Lipid Peroxidation and Antioximentioning
confidence: 77%
“…The mechanism of action of ranitidine is well known. Furthermore, an in vitro study confirmed that H 2 blockers such as ranitidine have limited cytoprotective ability independent of acid secretion [42]. Figure 3 shows MDA concentration in normal gastric mucosa and in gastric mucosa of non-pretreated rats and rats pretreated with OLE and ranitidine.…”
Section: Effect Of Ole Pretreatment On Lipid Peroxidation and Antioximentioning
confidence: 77%